Prediction of VO2max from a new field test based on portable indirect calorimetry - Flouris, A. D.; Metsios, G. S.; Famisis, K.; Geladas, N.; Koutedakis, Y. (Journal of Science and Medicine in Sport, 2010)
We assessed the validity and reliability of the new 15 m square shuttle run test (SST) for predicting laboratory treadmill test (TT) maximal oxygen uptake () compared to the 20 m multistage shuttle run test (MST) in 45 adult males. Thirty participants performed a TT and a SST once to develop a prediction model. The remaining 15 participants performed the TT and MST once and the SST twice for cross-validation purposes. Throughout testing was determined via portable indirect calorimetry while blood lactate concentration was assessed at the fifth recovery minute. Comparisons of TT (51.3 ± 3.1 ml kg-1 min-1) with SST measured (51.2 ± 3.2 ml kg-1 min-1) and predicted (50.9 ± 3.3 ml kg-1 min-1) showed no differences while TT blood lactate was higher compared to SST (10.3 ± 1.7 mmol vs. 9.7 ± 1.7 mmol, respectively). In contrast, MST measured (53.4 ± 3.5 ml kg-1 min-1) and predicted (57.0 ± 4.5 ml kg-1 min-1) and blood lactate (11.2 ± 2.0 mmol) were significantly higher compared to TT. No test-retest differences were detected for SST measured and predicted and blood lactate. It is concluded that the SST is a highly valid and reliable predictive test for.